ISLAMIC ISSUES SOCIAL RESPONSIBILITY ISLAMIC BANKING - MUKHLIS MUKHLIS; MAWADDAHIRHAM MAWADDAHIRHAM; SUGIANTO SUGIANTO; FUADAH BINTI JAUHARI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2022)
Islamic banking principally inculcates ethics and social and moral responsibility in doing business related to its principle function and disclosure with the whole purpose for the benefit of society. In the Islamic context, improving sharia-based community institutions and the Practice of Corporate Social Responsibility (CSR) will be seen. Disclosure of social responsibility is a way for companies to communicate with governments. In Islamic business, everyone is responsible before Allah for society. In the western concept, CSR is sometimes inseparable from the interests of gharar and social aspects. ISR has been disclosed on matters related to Islamic principles that are intermediary financial institutions, both individuals and institutions that are in one unit. And not allowed to exploit and harm others. Where Islamic banking must explain CSR funds using the ISR calculation system.This study uses a descriptive qualitative method by explaining CSR with the ISR model for Islamic banks to determine by using the system Increasing transparency in business operations by presenting accurate and actual information related to finance and paying attention to the spiritual level needs of Muslim investors or sharia compliance in decision making. Decisions as a form of accountability to Allah SWT and the community by creating a dynamic environment and paying attention to the community in the work area and the environment so that a high sense of social concern establishes a society that has religious capacity for Allah SWT.